Transseptal puncture in left atrial appendage closure guided by 3D printing and multiplanar CT reconstruction - Hozman, Marek; Herman, Dalibor; Zemanek, David; Fiser, Ondrej; Vrba, David; Poloczek, Martin; Varvarovsky, Ivo; Obona, Peter; Pokorny, Tomas; Osmancik, Pavel (Catheterization and cardiovascular interventions, 2023)
BACKGROUND: The presented study investigates the application of bi-arterial 3D printed models to guide transseptal puncture (TSP) in left atrial appendage closure (LAAC). AIMS: The objectives are to (1) test the feasibility of 3D printing (3DP) for TSP guidance, (2) analyse the distribution of the optimal TSP locations, and (3) define a CT-derived 2D parameter suitable for predicting the optimal TSP locations. METHODS: Preprocedural planning included multiplanar CT reconstruction, 3D segmentation, and 3DP. TSP was preprocedurally simulated in vitro at six defined sites. Based on the position of the sheath, TSP sites were classified as optimal, suboptimal, or nonoptimal. The aim was to target the TSP in the recommended position during the procedure. Procedure progress was assessed post hoc by the operator. RESULTS: Of 68 screened patients, 60 patients in five centers (mean age of 74.68 ± 7.64 years, 71.66% males) were prospectively analyzed (3DP failed in one case, and seven patients did not finally undergo the procedure). In 55 patients (91.66%), TSP was performed in the optimal location as recommended by the 3DP. The optimal locations for TSP were postero-inferior in 45.3%, mid-inferior in 45.3%, and antero-inferior in 37.7%, with a mean number of optimal segments of 1.34 ± 0.51 per patient. When the optimal TSP location was achieved, the procedure was considered difficult in only two (3.6%) patients (but in both due to complicated LAA anatomy). Comparing anterior versus posterior TSP in 2D CCT, two parameters differed significantly: (1) the angle supplementary to the LAA ostium and the interatrial septum angle (160.83° ± 9.42° vs. 146.49° ± 8.67°; p = 0.001), and (2) the angle between the LAA ostium and the mitral annulus (95.02° ± 3.73° vs. 107.38° ± 6.76°; p < 0.001), both in the sagittal plane. CONCLUSIONS: In vitro TSP simulation accurately determined the optimal TSP locations for LAAC and facilitated the procedure. More than one-third of the optimal TSP sites were anterior.
Keywords: výsledek terapie; transseptal puncture; Male; počítačová rentgenová tomografie; Aged; mužské pohlaví; senioři; left atrial appendage closure; computed tomography; Atrial Fibrillation; Treatment Outcome; Punctures; Tomography, X-Ray Computed; senioři nad 80 let; lidé; ženské pohlaví; Humans; síňové ouško; Aged, 80 and over; punkce; 3D tisk; Printing, Three-Dimensional; Atrial Appendage; Female; fibrilace síní; 3D printing